Convolutidae (Acoela) from Tanzania - Achatz, Johannes G.; Hooge, Matthew D. (Zootaxa, 2006)
Four species of Convolutidae, including a new genus and species, from shallow marine sediments in Tanzania are described: Convoluta enelitta, Convoluta thela comb. nov., Heterochaerus australis and Picola gen. nov. renei sp. nov. The species Conaperta krana and Conaperta thela are reassigned to the genus Convoluta.